The Role of the Mataram City Government in Improving Halal MSMEs Certification - Muttaqien, Furqon Zainul; Yanti Sandra Dewi, Novi; Agustina, Ahadiah (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research aims to dig deeper into the role of the Mataram City Government, especially through the Department of Industry, in improving halal certification for Micro, Small and Medium Enterprises (MSMEs). The main focus of this research is to understand the strategies and concrete steps taken by the Mataram City Department of Industry in supporting MSMEs to obtain halal certification, as well as their impact on the growth and development of MSMEs in Mataram City. In the data collection process, interview methods with stakeholders, including government officials and MSME owners, were used to obtain a comprehensive perspective on the efforts made by the Department of Industry. Apart from that, analysis of policy and program documents was also carried out to gain a deeper understanding of the policies that have been implemented and their impact on MSMEs. With this approach, it is hoped that the research results can provide a better understanding of the concrete contribution of the Mataram City Department of Industry in improving MSME halal certification, as well as provide valuable input for the development of more effective policies in the future. The research results show that the role of the Mataram city government in increasing the halal certification of MSMEs is Socialization and Assistance, Special Budget Allocation for Free Services, Quota for Issuing Free Halal Certificates, Collaboration Programs with the Central Government with Subsidies and with Private Parties.